1999
DOI: 10.1038/sj.ejcn.1600864
|View full text |Cite
|
Sign up to set email alerts
|

Dietary restraint and weight gain during pregnancy

Abstract: Objectives: To explore dietary intake and weight gain during pregnancy in relation to dietary restraint. Design: Longitudinal prospective study. Attitudes to weight gain during pregnancy were assessed using selfadministered questionnaires and dietary intake by 7-d weighed diet records in early and late pregnancy. Setting: South West London 1995 ± 1996. Subjects: 74 Caucasian pregnant women expecting their ®rst or second baby were recruited through a London hospital and data from 62 women were analysed. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 13 publications
2
51
1
Order By: Relevance
“…Results suggest that dietary restraint, an eating behavior that has been associated with weight changes outside of pregnancy (Hays & Roberts, 2008; Heatherton et al, 1991; Latner et al, 2007; Lawson et al, 1995), is related to GWG. Although previous studies have indicated a relationship between pre-pregnancy restraint and excessive GWG (Conway et al, 1999; Mumford et al, 2008), the present findings highlight the role of dietary restraint during pregnancy on GWG.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Results suggest that dietary restraint, an eating behavior that has been associated with weight changes outside of pregnancy (Hays & Roberts, 2008; Heatherton et al, 1991; Latner et al, 2007; Lawson et al, 1995), is related to GWG. Although previous studies have indicated a relationship between pre-pregnancy restraint and excessive GWG (Conway et al, 1999; Mumford et al, 2008), the present findings highlight the role of dietary restraint during pregnancy on GWG.…”
Section: Discussioncontrasting
confidence: 88%
“…Restraint also tends to increase during pregnancy (Fairburn, Stein, & Jones, 1992). Interestingly, although the restraint tends to be inversely correlated with weight gain, and thus might be related to lower GWG, elevated dietary restraint prior to pregnancy has been associated with excessive GWG (Conway et al, 1999; Mumford et al, 2008). However, the relationship between restrained eating and GWG has not been studied during pregnancy, only prior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of binge eating during pregnancy has significant effects on the mother’s health, particularly regarding GWG (Soares et al, 2009). Caucasian women deemed restrained eaters (i.e., those who frequently think about their diet and weight and make attempts to restrict their dietary intake) are significantly more likely than unrestrained eaters to exceed guidelines for recommended GWG (Conway et al, 1999), a finding that supports the hypothesis that pregnancy acts as a time for women to legitimize seemingly excessive food intake, disregarding any previous attitudes and intentions to eat less (Clark and Ogden, 1999). Similar to restrained eaters, dieters 4 have also been found to endorse more episodes of overeating during pregnancy, compared to non-dieters (Fairburn and Welch, 1990).…”
Section: Hypothesis 4: Craving Is Caused By Cultural and Psychosocialmentioning
confidence: 76%
“…Interestingly, the idea that pregnancy is a time when one does not need to feel accountable for one’s food intake, (i.e., a time of disinhibition), has been found to be most commonly endorsed by women classified as habitual dieters prior to pregnancy (Fairburn et al, 1992; Clark and Ogden, 1999; Mumford et al, 2008). Of note, it has been suggested that continuous pregravid dieting may affect the women’s ability to accurately distinguish hunger and satiety cues, which may contribute to excess energy intake in pregnancy (Mela and Rogers, 1998; Conway et al, 1999; Mumford et al, 2008). …”
Section: Hypothesis 4: Craving Is Caused By Cultural and Psychosocialmentioning
confidence: 99%